Body representation in people with apraxia post Stroke– an observational study. (21st March 2021) - Lane, Donncha; Tessari, Alessia; Ottoboni, Giovanni; Marsden, Jonathan
ABSTRACT: Objective : To investigate how two types of body representation (body schema and body image) were affected in people with and without apraxia following a supratentorial stroke. Design : Observational cross-sectional study Setting : Level 1 Specialist Neurological Rehabilitation Unit Participants : 30 participants post-stroke diagnosed with (n = 10) and without apraxia (n = 20) according to a modified version of the short Ideomotor Apraxia Test. Interventions : Not applicable Main Outcome Measures : Body schema assessed using the hand laterality recognition test and body part knowledge test; Implicit body image assessed using the sidedness test. Results : Left-sided lesions were more common in the apraxic group. Compared to people without apraxia post-stroke, those with apraxia showed significantly reduced accuracy and longer reaction times on the hand laterality test and fewer correct responses on the body part knowledge test. There was no between-groups difference in the sidedness test. Conclusions : People with apraxia showed deficits in online body representations (body schema) that are used to plan and execute actions. Future research studies could target body schema deficits as an adjunct in the rehabilitation of apraxia.